Anisotropic films of polypyrrole formed electrochemically using a non-planar dopant - Kassim, Anuar; Block, Harry; Davis, Fred J.; Mitchell, Geoffrey R. (1992)
We report the electrochemical preparation of electrically conducting films based on polypyrrole, using 10-camphorsulfonate as the dopant, which exhibit a highly anisotropic molecular organisation. This contrasts with earlier reports, in which anisotropy appeared to be restricted to films prepared using aromatic-based planar dopants. Possible growth mechanisms for these materials to account for the molecular anisotropy are discussed.